Efek Hipolipidemik Beras Parboiled Terfortifikasi Kromium, Magnesium dan Ekstrak Kayu Manis pada Tikus Diabetes - Herlyn Winda Wie Leba (Agritechnology, 2023)
Abstract Strategy for managing diabetic blood sugar is to eat low glycemic index (GI) foods such as parboiled rice. In addition, diabetic need adequate chromium and magnesium. Insulin resistance in diabetics results in impaired lipid metabolism, characterized by increased levels of cholesterol, triglycerides, and Low-Density Lipoprotein (LDL). The purpose of this study is to determine the effect of parboiled rice fortified with chromium, magnesium, and cinnamon on the hypolipidemic effects on diabetic rats. Clinical trial treatment on rats with dietary intake was given for 28 days in six groups, namely healthy rats with standard feed (TSPS), diabetic rats with standards feed (TDPS), diabetic rats with milled or non-parboiled rice (TDNP), diabetic rats with non-fortified parboiled rice (TDPNF), and diabetic rats with Cr, Mg, and cinnamon (TDPFK). The analysis performed included glucose, insulin, cholesterol, triglyceride, LDL, and High-Density Lipoprotein (HDL) levels. Statistical analysis of data using One Way Anova. After 28 days of treatment, it was found that in the TDPFK group, glucose levels decreased significantly (p<0.05) from 258.63 mg/dL to 111.19 mg/dL (57%), and 9.28 ng/mL to 1.96 (78.87%), while insulin levels increased significantly (p<0.05) from 413.97 ug/dL to 540.65 ug/dL (30.60%). In the TDPFK group, cholesterol, triglyceride, and LDL levels, respectively, decreased significantly (p<0.05) 53.21%, 41.45%, and 62.43%, and the percentage reduction was greater than that of the other treatment groups. HDL levels increased significantly (p<0.05) from 26.70 mg/dL to 78.65 mg/dL (194.50%) in the TDPFK group. Intake of parboiled rice fortified with chromium, magnesium, and cinnamon (TDPFK) can reduce blood glucose, cholesterol, triglyceride, and LDL levels and increase insulin and HDL levels. This type of feed can be use in the diet of diabetic. Keywords: Cholesterol, diabetic, fortified, hypolipidemic, parboiled rice